Study on the Braking Characteristics of Linear Induction Motors - Karaliunas, B. (Elektronika ir Elektrotechnika, 2012)
This paper presents the research results of the braking characteristics of linear induction motors. The spectrum analysis method of the magnetic fields is used. There were derived the expressions of the elementary components of the continuous spectrum amplitudes of the braking current volumic density and primary magnetic field as well as their characteristics were investigated. The assessment of the elementary components of higher frequency allows the increase of accuracy when calculating the characteristics of braking. For the simulation of the magnetic field of the dynamic braking there was applied the software package Maxwell. The received results indicates that there exist the transversal and longitudinal edge effects which influence the characteristics of braking. Ill. 7, bibl. 5 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.118.2.1172